2002
DOI: 10.1080/11250000209356457
|View full text |Cite
|
Sign up to set email alerts
|

Microcharon novariensis, a new microparasellid isopod from groundwater in Italy (Crustacea, Isopoda, Janiroidea)

Abstract: A new species of Microcharon from hyporheic waters of Piedmont, northern Italy, described herein as Microcharon novariensis sp. n., shows some affinities with the eastern Mediterranean group of Microcharon; its enigmatic origin and phylogenetic relationships are discussed. Microcharon marinus is for the first time recorded from the island of Elba.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…in the matrix refers to unknown character state. Contributions to Zoology, 76 (1) -2007(1) - Galassi, 1991Galassi et al, 1995a, b;Stoch and Galassi, 2002;Yacoubi et al, 1997).…”
Section: Historical Biogeography Origin and Agementioning
confidence: 99%
“…in the matrix refers to unknown character state. Contributions to Zoology, 76 (1) -2007(1) - Galassi, 1991Galassi et al, 1995a, b;Stoch and Galassi, 2002;Yacoubi et al, 1997).…”
Section: Historical Biogeography Origin and Agementioning
confidence: 99%
“…Previous works on phylogeny and biogeography of inland species have shown that species with more characters in an apomorphic state resulted from recent regressions whereas species exhibiting more plesiomorphic character states were left by ancient marine withdrawal during the late Cretaceous period (Coineau 1994, Galassi et al 1995b, Stoch & Galassi 2002. Vicariance evolution may have worked at different scales of space and time: at the scale of the Mediterranean, plate tectonics and large transgressions resulted in different lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the genus Microcharon Karaman, 1933 has a worldwide distribution, from Polynesia and New Caledonia to Europe, the Mediterranean, the Caribbean and the Galapagos (Delamare Deboutteville 1960, Coineau 1986, Stock 1977, Galassi 1991, Galassi et al 1995a. More than 70 species are known from the Mediterranean basin alone both in the northern and the southern areas (Argano & Pesce 1979, Pesce & Galassi 1988a, b, 1990, Pesce & Tetè 1987, Galassi 1991, Coineau 1994, Galassi et al 1995a, b, Boulanouar et al 1995, Yacoubi Khebiza et al 1997, 1999, Stoch & Galassi 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation